The Political Economy of Domestic Tax Reform in Bangladesh: Political Settlements, Informal Institutions and the Negotiation of Reform. Issue 12 (1st December 2016) - Hassan, Mirza; Prichard, Wilson
ABSTRACT: This paper explains the persistence of a tax system characterised by low revenue collection and extensive informality in Bangladesh. It combines analysis of long-term formal and informal institutions and of micro-level incentives shaping negotiation of short-term reform. The system is unusually informal, discretionary, and corrupt, but remains resistant to change because it delivers low and predictable tax rates to business, extensive opportunities for corruption to the tax administration, and an important vehicle for fundraising by political leaders and rent distribution to their elite supporters. We then explore the dynamics of micro-level reform and external pressure within the constraints of this overarching political bargain.